Strategic Design and Innovative Thinking in Business Operations The Role of Business Culture and Risk Management (Contributions to Management Science,, 2018)
Recently, rapid technological advances have been influencing the global business operations strategies at companies of all sizes like never before. At the same time, there has been a shift in business cultures due to the rising prevalence of matrix organizations and innovative thinking. This book investigates the role of these factors in shaping the business operations of tomorrow. To address the topic comprehensively, the editors have gathered expert contributions exploring the following dimensions: the business and organizational environment, strategic design, innovativeness and risk management. Discussing aspects ranging from customer selection to understanding regional, national and supranational market dynamics, the contributions will help readers understand both the complexity of and opportunities presented by designing operations. .